2017
DOI: 10.1016/j.jacc.2017.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Early Invasive Versus Selective Strategy for Non–ST-Segment Elevation Acute Coronary Syndrome

Abstract: In patients with NSTE-ACS and elevated cardiac troponin T levels, an early invasive strategy has no benefit over a selective invasive strategy in reducing the 10-year composite outcome of death or spontaneous MI, and a selective invasive strategy may be a viable option in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 24 publications
0
29
0
1
Order By: Relevance
“…There remains a substantial opportunity to improve ACS outcomes especially in high-risk patients. An aggressive approach to ACS and AF management, including selective elective strategy, optimal use of P2Y12 inhibitor and non-vitamin K antagonist oral anticoagulant, or timely rhythm conversion is justified and should be balanced with the risk associated with aging and co-morbidity [ 28 30 ]. There is a growing need for randomized controlled trial data to be more representative of the elderly patients or patients with multiple co-morbidities.…”
Section: Discussionmentioning
confidence: 99%
“…There remains a substantial opportunity to improve ACS outcomes especially in high-risk patients. An aggressive approach to ACS and AF management, including selective elective strategy, optimal use of P2Y12 inhibitor and non-vitamin K antagonist oral anticoagulant, or timely rhythm conversion is justified and should be balanced with the risk associated with aging and co-morbidity [ 28 30 ]. There is a growing need for randomized controlled trial data to be more representative of the elderly patients or patients with multiple co-morbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Several other trials also showed no significant effect in cardiovascular outcome [19][20][21]. Importantly, one of the largest of these trials [20] established a significant reduction in the combined endpoint of death MI and stroke at 6 months for patients with the highest risk defined as having a GRACE score N 140, an effect that was lost at 10-year follow-up [22].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with a previous Cochrane analysis published in 2016 [ 3 ]. However, this prior analysis did not include the new long-term data from the FRISC-II [ 4 ], RITA-3 [ 5 ] and ICTUS [ 6 ] trials, which have been published recently.…”
Section: Discussionmentioning
confidence: 99%